Probing on the Stable Structure of Silicon-Doped Charged Magnesium Nanomaterial Sensor: SiMgn±1 (N = 2−12) Clusters DFT Study - Zeng, Lu; Wei, Xiao-Fan; Liang, Mei-Kun; Zhao, Jun; Zhu, BenChao (Frontiers in Materials, 2020)
The stable structures of silicon-doped charged magnesium nanomaterial sensor, SiMg±1 n(n=2-12) clusters, were systematically investigated using the CALYPSO approach coupled with density functional theory (DFT). The growth mechanism of SiMg±1 n(n=2-12) nanosnsors shows that the tetrahedral and tower-like structures are two basic structures, and almost all other clusters’ geometries are based on their variants. Most importantly, the fascinating SiMg-1 8and SiMg+1 8clusters are obtained through stability calculations of all the lowest energy state of clusters. These two clusters show the strongest local stability and thus can be served as reliable candidates for experimentally fabricated silicon-doped magnesium nanosensor. Electronic structural properties and chemical bonding analysis are also adopted to further study the stability of SiMg-1 8and SiMg+1 8 nanosensors. The theoretical calculations of infrared (IR) and Raman spectra of SiMg-1 8and SiMg+1 8clusters show that their strongest spectral frequencies are distributed in the range of 80 – 240 cm-1. We believe that our studies will stimulate future synthesis of silicon-doped magnesium in IoT nanosensors.